Menumbuhkan Spirit Filantropi Siswa SMA Muhammadiyah 1 Blitar - Abdul Rozak Ali Maftuhin (Jurnal Budi Pekerti Agama Islam, 2025)
Character education is essential to foster good attitudes and habits among students, including social awareness (philanthropy). This study aims to explore more deeply how schools internalize philanthropic values through their programs. The research approach used is qualitative research with a case study type. The researcher used structured interviews, documentation, and observation with teachers and students to collect data. The results of the study show that efforts to foster a philanthropic spirit through school programs at SMA Muhammadiyah 1 Blitar have been successfully implemented, with programs such as the Friday Infaq, Smamone Cares, and the Blessing Can aimed at fostering empathy for others and instilling a habit of social care. These results are reinforced by changes in student attitudes, such as increased responsiveness and initiative in events requiring social assistance.